Effectiveness of Simeprevir plus Sofosbuvir, With or Without Ribavirin, in Real-World Patients with HCV Genotype 1 Infection. - Sulkowski, M S; Vargas, H E; Di Bisceglie, A M; Kuo, P A; Reddy, K R; Lim, J K; Morelli, G; Darling, J M; Feld, J J; Brown, R S; Frazier, L M; Stewart, T G; et al. (Gastroenterology, 2015)
The interferon-free regimen of simeprevir plus sofosbuvir was recommended by professional guidelines for certain patients with hepatitis C virus (HCV) genotype 1 infection based on the findings of a phase 2 trial. We aimed to evaluate the safety and efficacy of this regimen in clinical practice settings in North America.